KARAKTERISTIK PENURUNAN FLUKS PADA FILTRASI LARUTAN HUMIC ACID DENGAN MEMBRAN MIKROFILTRASI - A Ardiansyah; Ario Budi Kusumo; I Nyoman Widiasa (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Natural surface water is containing various organic matter. One of them is Humic Acid (HA) which is known as the major cause of fouling in membrane filtration, and proved carcinogenic to human body. This study is carried to characterize flux reduction of HA filtration with Microfiltration Membrane. The analysis in the research is carried out by flux and absorbancy measuring. From this study the following conclusion can be taken; highest flux reduction are detected in the first 5 minutes of operations then slows down in the 15th minutes and later, where higher the HA solution concentration, will result in higher flux reduction. With the HA 5 ppm and HA 25 ppm’s J/Jw in 0,49 and 0,25, respectively in the 120th minutes. The addition of ion CaSO4 slows the rate of flux reduction, where it shows J/Jw of 0,051in the 120th minute. For filtration in different pressure, higher the pressure will result ini higher rate of flux reduction too., While in filtration of HA solution in different pH, highter the pH will result in the lowering the rate of reduction of flux. In the addition of ozone injection, the experiment carried shows that ozone addition is not giving any significant change on flux reduction.